2020
DOI: 10.7554/elife.55792
|View full text |Cite
|
Sign up to set email alerts
|

An improved zebrafish transcriptome annotation for sensitive and comprehensive detection of cell type-specific genes

Abstract: The zebrafish is ideal for studying embryogenesis and is increasingly applied to model human disease. In these contexts, RNA-sequencing (RNA-seq) provides mechanistic insights by identifying transcriptome changes between experimental conditions. Application of RNA-seq relies on accurate transcript annotation for a genome of interest. Here, we find discrepancies in analysis from RNA-seq datasets quantified using Ensembl and RefSeq zebrafish annotations. These issues were due, in part, to variably annotated 3' u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 67 publications
(86 reference statements)
5
90
0
Order By: Relevance
“…C. Length of extended 3' UTR regions for Lawson et al 2020 and this study show similar distribution. Supplementary Figure 6.…”
Section: Competing Interest Statementsupporting
confidence: 75%
See 1 more Smart Citation
“…C. Length of extended 3' UTR regions for Lawson et al 2020 and this study show similar distribution. Supplementary Figure 6.…”
Section: Competing Interest Statementsupporting
confidence: 75%
“…RNA-seq track shows merged replicates at 20-25 somites. Ensembl GRCz11.98 and Lawson et al 2020 annotations are shown, together with extracted extended 3' UTR region from Lawson et al and this study. In this study, transcriptome assembly using StringTie was used to find extended 3' UTR regions using White et al 2017 RNA-seq data. B.…”
Section: Competing Interest Statementmentioning
confidence: 96%
“…Recent studies have established distinct roles for vcla and vclb during zebrafish heart development, which reflect their expression in the myocardium and epicardium, respectively (Cheng et al, 2016; Fukuda et al, 2019b; Han et al, 2017). In contrast, in the endothelium vcla and vclb are co-expressed (Lawson et al, 2020) and, consistent with this, we did not notice phenotypic variation in different mutant allele combinations (e.g. vcla -/- ;vclab +/- vs. vcla +/- ;vclab -/- ) with regard to the appearance of junctional fingers - in agreement with the notion that vcla and vclb mutants can genetically compensate for each other (El-Brolosy et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…S2A) and both show enriched expression in RNA-seq from isolated kdrl:mcherry-positive cells, consistent with their recently described endothelial expression in zebrafish (Fig. 1I; Lawson et al, 2020;Stratman et al, 2020). By contrast, pdgfrb is enriched in pdgfrb:citrine cells from the same larvae (Fig.…”
Section: Pdgfb/pdgfrb Signaling Is Required For Zebrafish Brain Pericyte Developmentsupporting
confidence: 87%